Lipid metabolism abnormalities in pediatric abdominal solid malignant tumors: a comprehensive review - Hao, Qiang; Han, Lu; Mi, Wenrui; Hu, Tingting; Lin, Aiqin; Liu, Jie (Frontiers in Pediatrics, 2025)
Pediatric abdominal solid tumors mainly include neuroblastoma, nephroblastoma, hepatoblastoma, and rhabdomyosarcoma. Although significant progress has been made in the treatment of these tumors with the combination of surgery and chemotherapy, the treatment outcomes for some patients remain unsatisfactory, and the mortality rate for late-stage patients is still high. The diagnosis and treatment of abdominal solid tumors remain one of the key challenges in pediatric oncology. Numerous studies have found that lipid metabolism abnormalities in tumor tissues and cells lead to a significant increase in lipid levels, promoting cell proliferation, tumor progression, and chemoresistance. This review focuses on the recent advances in the study of lipid metabolism abnormalities in pediatric abdominal solid tumors, aiming to provide a theoretical basis for the treatment of these tumors.